2013
DOI: 10.1063/1.4773327
|View full text |Cite
|
Sign up to set email alerts
|

Runup and boundary layers on sloping beaches

Abstract: The present study is devoted to discrepancies between experimental and theoretical runup heights on an inclined plane, which have occasionally been reported in the literature. In a new study on solitary wave-runup on moderately steep slopes, in a wave tank with 20 cm water depth, detailed observations are made for the shoreline motion and velocity profiles during runup. The waves are not breaking during runup, but they do break during the subsequent draw-down. Both capillary effects and viscous boundary layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…On the other hand, a flow determined to be stable by one of the above criteria might display instabilities once the initial amplitude is equal or larger than its amplification. In their related study on boundary layers on a 10 • beach Pedersen et al (2013) reported (section IVA) for one case (incident wave with = 0.3) that instability occurred in an up-beach position, immediately after an inflection point in the boundary layer profile was observed. However, this was observed in 3 out of 4 experiments, and never in a location close to equilibrium shoreline, where inflection points in the retardation phase were also present.…”
Section: Linear Stability Of the Boundary Layer Flow Under A Solitarymentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, a flow determined to be stable by one of the above criteria might display instabilities once the initial amplitude is equal or larger than its amplification. In their related study on boundary layers on a 10 • beach Pedersen et al (2013) reported (section IVA) for one case (incident wave with = 0.3) that instability occurred in an up-beach position, immediately after an inflection point in the boundary layer profile was observed. However, this was observed in 3 out of 4 experiments, and never in a location close to equilibrium shoreline, where inflection points in the retardation phase were also present.…”
Section: Linear Stability Of the Boundary Layer Flow Under A Solitarymentioning
confidence: 99%
“…The code was written in MATLAB and we verified the above algorithm by a test problem as well as comparison with the boundary layer model of Pedersen et al (2013), which again was compared to measurements.…”
Section: Boundary Layer Equations Solvermentioning
confidence: 99%
See 3 more Smart Citations